2020
DOI: 10.1155/2020/7410797
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Lifestyle Interventions for Preventing Diabetes in a Health Resource-Limited Setting

Abstract: Aims. Type 2 diabetes mellitus (T2DM) is a health challenge in China, and the economic outcomes of lifestyle intervention are critically important for policymakers. This study estimates the lifetime economic outcomes of lifestyle intervention among the prediabetic population in the Chinese context. Methods. We developed a mathematical model to compare the cost-effectiveness of lifestyle intervention and no prevention in the prediabetic population. Efficacy and safety, medical expenditure, and utility data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Sensitivity analyses were performed on all variables associated with disease prevalence, screening effectiveness, transition probability between states, costs, and discount rate. When there was no available data range, 75–125% of the initial parameters were taken as the variation range of the parameters for sensitivity analysis ( 43 ). Furthermore, the screening compliance rate is essential, and we assume it is 100% in the base model.…”
Section: Methodsmentioning
confidence: 99%
“…Sensitivity analyses were performed on all variables associated with disease prevalence, screening effectiveness, transition probability between states, costs, and discount rate. When there was no available data range, 75–125% of the initial parameters were taken as the variation range of the parameters for sensitivity analysis ( 43 ). Furthermore, the screening compliance rate is essential, and we assume it is 100% in the base model.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted one-way and probabilistic sensitivity analyses to explore the effect of parameter uncertainty [30][31][32]. In the one-way sensitivity analyses, we used the minimum and maximum estimates for all key parameters, testing the in uence of extreme variations in each parameter on the overall results.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Several reviews conducted in high-income countries reported that health behavior interventions, including those focusing on diet and physical activity, are cost-effective for the management and treatment of T2DM [ 22 , 23 , 24 ]. Health behavior interventions also reduce the probability of developing T2DM by 9.53% and have additional positive outcomes on life expectancy, quality-adjusted life year (QALY), and total cost savings over a lifetime [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%